A guide to the performance of Love and Light by Brian Balmages - Middleton, Ryan James, author; Phillips, Rebecca L., advisor; Grapes, K. Dawn, committee member; Mallette, Dawn, committee member; Taylor, Jayme, committee member (Colorado State University. Libraries, 2022)
Brian Balmages is a renowned American composer in the band profession. This thesis is the first formal study of Brian Balmages and his compositions. The author provides a detailed biographical account of the composer's musical background as well as an overview of his works and contributions to music education, both derived from an interview and written communication with Balmages. Although Balmages is well known for his significant contributions to the repertoire of developing ensembles, his 2020 composition Love and Light exemplifies his ability to express his compositional voice in a more intricate and expansive setting. The piece was commissioned in January 2019 by Elizabeth Elliott. This document provides a detailed account of the inception and premiere of the piece, based primarily on interviews with Elliott and Balmages. These personal accounts are vital in understanding the impact of the piece both within and beyond the music community. A detailed theoretical analysis of Love and Light completes this study, covering a wide array of musical elements, including form, melody, harmony, rhythm, orchestration, texture, dynamics, and use of borrowed musical material. Throughout the theoretical analysis, rehearsal and performance considerations for conductors and ensemble members are highlighted.
Keywords: Balmages, Brian; light; analysis; love